Finding linkages between the Sustainable Development Goals in Uganda: a key to attain health and well-being for all - Daniel Helldén; Tobias Alfvén; Rawlance Ndejjo; Rhoda K Wanyenze; Irene Wanyana; Marat Murzabekov; Nina Viberg (BMJ Publishing Group, 2024)
Introduction While Uganda has made significant strides towards the 2030 Agenda, several development challenges persist, including a high disease burden, poverty and the effects of climate change. Multisectoral collaboration is critical in achieving Uganda's Sustainable Development Goals (SDGs); however, most sectors in the country still operate in isolation. Understanding the linkages between the goals in Uganda is critical for accelerating progress on health and the SDGs. This study aimed at taking initial steps in investigating the linkages between health and other SDGs in Uganda.Methods A 2-day workshop with 29 multisectoral stakeholders was conducted to explore the nature of linkages between the SDGs nationally in Uganda. Results were analysed using the SDG synergies approach and presented using a cross-impact matrix to show the nature and strength of linkages between the goals.Results Overall, there were more positive linkages between the SDGs than negative ones. Progress on SDG 10 (reduced inequalities) was considered to have the most positive influence on the 2030 Agenda. SDG 3 (good health and well-being) was the goal that was perceived to be most positively affected if progress was made on other goals. The economic goals, SDG 8 (decent work and economic growth) and SDG 9 (industry, innovation and infrastructure) were the goals that promoted other goals the least. Negative linkages were perceived between SDG 13 (climate action) and the economic goals (SDG 8; SDG 9).Conclusion The findings reveal that promoting linkages were perceived to be the majority, but some restricting linkages between the SDGs also exist. The promoting linkages suggest a need for integrated approaches in attaining SDG 3 and other SDGs in Uganda. Further addressing inequalities in their different forms, policy reforms, local community engagements and continuous monitoring are critical for sustainable development in Uganda.